Revising a Display of Multidimensional Laboratory Measurements to Improve Accuracy of Perception - Hoaglin, D. C. (Methods of Information in Medicine, 1993)
To display multidimensional laboratory measurements, Hoeke et al. (1991) proposed a technique that uses plotting axes radiating from a point, assigns each test to a separate axis, and links the test results with line segments. A special nonlinear scaling ensures that a patient whose results all fall in the normal range is represented by a regular polygon of middle size, and colored zones emphasize more serious departures from the normal range. Results of research in graphical perception, however, point to potential difficulties in clinical applications. Those results also suggest a revision of the display that should overcome the difficulties. The new version plots the test results on parallel horizontal lines and links the points for adjacent tests by line segments, while retaining the special scaling and the colored bands.
Keywords: Clinical Laboratory; Graphical Perception; Graphical Representation